Working visit to Kebun Kota Sdn Bhd - Mohd Nizam, Abdul Rashid (Penerbit UMP, 2015)
Research Development and Commercialisation (R&D&C) involved a lot of work and effort. It needs drive and dynamism. To ensuresuccess, it is critical to develop and instilteamwork practices that surpass traditional-silowaysthat have divided the academia, industry, government and society for decades.